Pharmaceutical Activity of Medicinal Plant Amaranthus viridis Linn. Due to Its Chemical Constituents: A Review - Haider, Ali; Ikram, Muhammad; Fatima , Urooj; Javed, Asma (Universitas Muhammadiyah Prof. Dr. Hamka, 2023)
Background: Amaranthus viridis, a herbal plant belonging to the family Amaranthaceae, has gained significant attention in the field of traditional medicine due to its rich chemical composition. This plant is known to contain various bioactive components that contribute to its pharmaceutical value. With its extensive range of chemical compounds, Amaranthus viridis has found applications in therapeutic, pharmaceutics, and cosmetic industries. In this study, we aim to explore the medicinal potential of Amaranthus viridis and investigate its various pharmaceutical activities. Methods: The process of writing this review involved conducting comprehensive electronic research using reputable sources, including international and national article databases, along with books accessed through platforms like Google Scholar, PubMed, IEEE Xplore, ScienceDirect and others. The gathered data is subsequently analyzed, followed by employing synthetic approaches with narrative methods to derive meaningful conclusions and interpretations. Results: Amaranthus viridis displays potent antioxidant and anti-inflammatory properties, attributed to its rich composition of flavonoids, cardiac glycosides, and zinc. Its diverse pharmaceutical activities make it a promising contender for medicinal use, addressing labor pain, skin conditions like eczema and psoriasis, and respiratory issues, while also exhibiting antimicrobial effects against bacteria, fungi, and parasites. It can be accomplished by Extraction with solvent, Phytochemical screening and Isolation and purification. Conclusion: Amaranthus viridis, a herbal plant, shows significant potential in therapeutic, pharmaceutics, and makeup industries. Its bioactive compounds, including flavonoids, cardiac glycosides, and zinc, contribute to its diverse pharmaceutical activities, such as antioxidant, anti-inflammatory, antibacterial, antifungal, antidiabetic, and antihelmintic properties.